Renin-angiotensin system activation correlates with microvascular dysfunction in a prospective cohort study of clinical sepsis - Doerschug, Kevin C (BioMed Central, 2010)
INTRODUCTION: Microvascular dysregulation characterized by hyporesponsive vessels and heterogeneous bloodflow is implicated in the pathogenesis of organ failure in sepsis. The renin-angiotensin system (RAS) affects the microvasculature, yet the relationships between RAS and organ injury in clinical sepsis remain unclear. We tested our hypothesis that systemic RAS mediators are associated with dysregulation of the microvasculature and with organ failure in clinical severe sepsis. METHODS: We studied 30 subjects with severe sepsis, and 10 healthy control subjects. Plasma was analyzed for plasma renin activity (PRA) and angiotensin II concentration (Ang II). Using near-infrared spectroscopy, we measured the rate of increase in the oxygen saturation of thenar microvascular hemoglobin after five minutes of induced forearm ischemia. In so doing, we assessed bulk microvascular hemoglobin influx to the tissue during reactive hyperemia. We studied all subjects 24 hours after the development of organ failure. We studied a subset of 12 subjects at an additional timepoint, eight hours after recognition of organ failure (early sepsis). RESULTS: After 24 hours of resuscitation to clinically-defined endpoints of preload and arterial pressure, Ang II and PRA were elevated in septic subjects and the degree of elevation correlated negatively with the rate of microvascular reoxygenation during reactive hyperemia. Early RAS mediators correlated with microvascular dysfunction. Early Ang II also correlated with the extent of organ failure realized during the first day of sepsis. CONCLUSIONS: RAS is activated in clinical severe sepsis. Systemic RAS mediators correlate with measures of microvascular dysregulation and with organ failure.